Conflict and Difference in Nineteenth-Century Literature
X, 257 p.
Keywords: How should we understand Victorian conflict? The Victorians were divided between multiple views of the political, religious and social issues that motivated their changing aspirations. Such debates are a fundamental aspect of the literature of the period and these essays propose new ways of understanding their significance.